Tax incentives and green innovation—The mediating role of financing constraints and the moderating role of subsidies - Wang, Cong; Chen, Pengyu; Hao, Yuanyuan; Dagestani, Abd Alwahed (Frontiers in Environmental Science, 2022)
Government intervention is increasingly vital due to the dual externalities of green innovation. We explored the relationship between tax incentives, subsidies, and green innovation. Based on data from Chinese listed companies from 2010 to 2019, we developed an evaluation system for corporate green innovation. First, we find that tax incentives promote corporate green innovation, while subsidies have little effect on green innovation. Second, we find that financing constraints are the main path of influence of tax incentives. Also, subsidies reverse the positive impact of tax incentives. Third, we further explore the heterogeneity of firms. We find that tax incentives and subsidies only impact green innovation by state-owned enterprises, monopolies, and small and medium-sized enterprises. We hope to provide new theoretical insights into intervention policy improvements and corporate green innovation in developing countries such as China.